Forward equations for option prices in semimartingale models - Cont,R; Bentata,A (Finance and Stochastics, 2015)
We derive a forward partial integro-differential equation for prices of calloptions in a model where the dynamics of the underlying asset under the pricing measure is described by a -possibly discontinuous- semimartingale. A uniquenesstheorem is given for the solutions of this equation. This result generalizesDupire's forward equation to a large class of non-Markovian models with jumps.